2012
DOI: 10.3855/jidc.1676
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative antibiotic prophylaxis practice and guideline adherence in Jordan: a multi-centre study in Jordanian hospitals

Abstract: Introduction: The use of antimicrobial prophylaxis for surgical procedures is one of the measures employed to prevent the development of surgical site infections (SSI). The appropriate choice of antimicrobial agents, dosage regimen, timing, duration and use of intravenous route must be evidence based. This study aimed to assess the practice of surgical antibiotic prophylaxis and adherence of practitioners to the American Society of HealthSystem Pharmacists (ASHP) guidelines for antimicrobial prophylaxis in sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 18 publications
6
36
1
3
Order By: Relevance
“…All the above findings suggested that the antimicrobial prophylaxis was clearly overused in our study, which was similar to the findings of several earlier studies which had reported an overuse and/or misuse of the preoperative antimicrobials in different countries [12]. Various measures like the development of local hospital guidelines, surveillance on SSIs, educational interventions, hospital antibiotic policy, promoting good surgical techniques and strict asepsis in the operating theatre, are suggested to prevent the emergence of multiresistant organisms [14].…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…All the above findings suggested that the antimicrobial prophylaxis was clearly overused in our study, which was similar to the findings of several earlier studies which had reported an overuse and/or misuse of the preoperative antimicrobials in different countries [12]. Various measures like the development of local hospital guidelines, surveillance on SSIs, educational interventions, hospital antibiotic policy, promoting good surgical techniques and strict asepsis in the operating theatre, are suggested to prevent the emergence of multiresistant organisms [14].…”
Section: Resultssupporting
confidence: 81%
“…Very similar to most of the previous studies, the main parameter of concern which was noted in our study was the prolonged duration of the antibiotic prophylaxis [7,9,12,22]. Overall, only 10 (3.9%) patients in our study received the antimicrobials for less than 36 hours, inspite of the published guidelines which had recommended discontinuation of the prophylaxis within 24-48 hours [17].…”
Section: Referencescontrasting
confidence: 33%
See 2 more Smart Citations
“…6 However, despite the presence of evidence-based guidelines, poor adherence to guidelines has been reported internationally. [7][8][9][10][11][12][13] The King Hussein Cancer Centre (KHCC) in Amman, Jordan, is a 170-bed comprehensive teaching cancer centre with a surgical service consisting of nine teams with various specialties. Among these teams, an average of 25 patients are seen and five major elective surgeries are performed per day.…”
mentioning
confidence: 99%